Pengaruh Saving Behavior dan Literacy Finance Terhadap Retirement Preparedness pada Karyawan Swasta di PT. FCC Indonesia - Yusuf Zulkarnaen; Rengga Madya Pranata; Ujang Suherman (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to find out how saving habits and financial literacy at PT. FCC Indonesia private workers influence their preparation for retirement. This research methodology combines purposive sampling and survey methodology with a quantitative descriptive approach. Because retirement readiness must be prepared from an early age, the object of research is PT FCC Indonesia, with a sample size of 100 respondents aged 20 to 40 years. The findings of this study indicate that saving and financial literacy significantly improve a person's preparation for retirement. Although financial literacy is necessary to increase awareness of money and can help people make the right financial decisions, including the decision to invest in retirement, saving behavior is very important to grow savings that can be used to meet living expenses in retirement. The fact that this research is limited to PT. FCC Indonesia and its small sample size is one of its weaknesses. In order for the research findings to be applied more widely, larger sample sizes and more geographic locations should be used in future research. Based on research findings, private employees at PT. FCC Indonesia's preparation for retirement is greatly influenced by their savings and financial literacy. This is consistent with other research which finds a positive correlation between saving behavior, financial literacy, and retirement preparation. Knowledge about the variables that influence private employees' retirement preparations is further advanced through this research. This study implies that to ensure private sector employees' financial readiness for retirement, it is important to increase their level of financial literacy and saving behavior.